2019
DOI: 10.1093/europace/euz028
|View full text |Cite
|
Sign up to set email alerts
|

QT as a predictor of recurrence after atrial fibrillation ablation and the impact of amiodarone: results from the placebo-controlled AMIO-CAT trial

Abstract: Aims Prolonged corrected QT interval (QTc) might be associated with arrhythmia recurrence after atrial fibrillation (AF) ablation. The effect of short-term amiodarone in this setting remains unknown. This study seeks to quantify short-term amiodarone’s impact on QTc, and to investigate QTc and amiodarone treatment as predictors of recurrence of arrhythmia after ablation. Methods and results The Short-term AMIOdarone treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Abnormal QT interval can cause ventricular myocardial conduction and automaticity abnormalities, leading to various arrhythmias. Søren Zo ga Diederichsen et al (63)conducted pre-and post-operative QTc measurements on 212 patients who underwent RFA surgery and found that, after a 3-month blanking period, the recurrence rate of patients with prolonged QTc was 63%, while the recurrence rate of patients with normal QTc was 41%. Baseline QTc prolongation was independently associated with the first recurrence of AF/AT after ablation (hazard ratio [HR] 2.06, P = 0.035).…”
Section: Qt Intervalmentioning
confidence: 99%
“…Abnormal QT interval can cause ventricular myocardial conduction and automaticity abnormalities, leading to various arrhythmias. Søren Zo ga Diederichsen et al (63)conducted pre-and post-operative QTc measurements on 212 patients who underwent RFA surgery and found that, after a 3-month blanking period, the recurrence rate of patients with prolonged QTc was 63%, while the recurrence rate of patients with normal QTc was 41%. Baseline QTc prolongation was independently associated with the first recurrence of AF/AT after ablation (hazard ratio [HR] 2.06, P = 0.035).…”
Section: Qt Intervalmentioning
confidence: 99%